Problematika stanovení bezpečných resekčních okrajů u nádorů parenchymatózních orgánů - Hermanová, M; Matěj, R; Dušková, J; Honsová, E; Tichý, M (Rozhledy v chirurgii, 2014)
The definition of a safe surgical margin in tumours of parenchymatous organs has been the subject of frequent debates and a number of studies. This topic is not generally unified for parenchymatous organs and has many organ specifics. Moreover, there are still controversies in the diagnostic criteria and the definitions of positive resection margins, in indications of perioperative examinations of resection margins, and in the prognostic significance of margin involvement in different parenchymatous organs. The consensus in terminology and standardization of histopathological examination procedures is also very desirable across the diagnostic areas.
Keywords: Neoplasm, Residual; lokální recidiva nádoru; Neoplasms; Risk Factors; prognóza; rizikové faktory; lidé; Neoplasm Recurrence, Local; reziduální nádor; Humans; nádory; Prognosis